DIFFERENT APPROACHES IN DEFINING THE ESSENCE AND CONTENT OF THE CONCEPT "NATIONAL SELF-CONSCIOUSNESS OF FUTURE TEACHERS" - O.V. Popruga (Academy of Cognitive and Natural Sciences, 2022)
The article deals with the problem o f formation o f national self-consciousness of a future teacher. The essence of the notion "national self-consciousness of a future teacher" and its structure have been revealedThe determinants of formation o f national self-consciousness o f a future teacher have been ascertained.